IDEOLOGI HUKUM DAN KEKUASAAN PADA WACANA PEMBERITAAN KASUS HUKUM DALAM MAJALAH TEMPO EDISI JULI 2012 - Desiana, Novita (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
The purpose of this study was (determine the form of legal ideology which is espoused by the journalists. Of tempo magazine, and (2) to determine whether there is an element of power or not. The approach in this study was critical paradigm is an elemnt of power or not. The approach in this study was critical paradigm with methods of critical discourse analysis (AWK). The sources of this research are four discourses news text about the law in the July 2012 edition of Tempo magazine. Furthermore the form of research data are vocabulary, phrases, or sentences that were analyzed by the following steps: transibing the data from the document (text message), grouping/classifying wors, phrases, or sentences as well as the background image of cases conditions raised in the reporting containing legal ideology, draw conclusions. The results of this study indicate that in the case of news contains legal ideology that is more pro and justice, and does not contain the characteristics of power in the reporting. The critical acumen of journalists in highlighting the problems in its message is just as form of selfi-identity of Tempo magazine with no affiliation to the government. This legal ideology appears in the way of selecting the vocabulary, phrases, sentences and citations that led to participant in the news, as well as the background image of cases conditions that appear in news.